High transcript levels of vitamin D receptor are correlated with higher mRNA expression of human beta defensins and IL-10 in Mucosa of HIV-1-exposed seronegative individuals (2013)
Vitamin D (VitD) is an endogenous immunomodulator that could protect from HIV-1 infection reducing immune activation and inducing the expression of anti-HIV-1 peptides. To establish a correlation between VitD and natural resistance to HIV-1 infection, a case-control study using blood and mucosa samples of 58 HIV-1-exposed but seronegative (HESN) individuals, 43 HIV-1 seropositives (SPs) and 59 non-exposed healthy controls (HCs) was carried out. The VitD concentration in plasma was determined by ELISA, and mRNA relative units (RU) of VDR, IL-10, TGF-ß, TNF-a and IL-1ß in peripheral blood mononuclear cells (PBMCs), oral and genital mucosa was quantified by qRT-PCR. mRNA levels of human beta-defensin (HBD) -2 and -3 were previously reported and used for correlations. Significantly higher levels of VitD were found in plasma as well as higher mRNA RU of VDR in PBMCs, and in genital mucosa from HESN compared to HCs. In addition, higher mRNA RU of TNF-a, IL-1ß and IL-10, and lower mRNA RU of TGF-ß were found in PBMC from HESNs compared to HCs. We also observed higher IL-10 mRNA RU in genital mucosa of HESNs compared to HCs, and the mRNA levels of TNF-a in oral and genital mucosa of SPs were higher compared to HESNs. Furthermore, positive correlations between VDR and IL-10 mRNA RU in PBMCs and genital mucosa of HESNs were found. Finally, HBD-2 and HBD-3 mRNA RU were positively correlated with VDR mRNA expression in oral mucosa from HESNs. These results suggest that high levels of VitD and its receptor are associated with natural resistance to HIV-1 infection. Up-regulation of the anti-inflammatory IL-10, and the induction of anti-HIV-1 defensins in mucosa might be part of the mechanisms involved in this association. However, further studies are required to define causal associations. Copyright: © 2013 Aguilar-Jiménez et al.